Effect of scarification treatments on seed germination of guava (Psidium guajava) - SOURABH, SOURABH; PREETI, PREETI; SHARMA, JEET RAM; BHUKAR, AXAY (The Indian Journal of Agricultural Sciences, 2020)
The present study was carried out to investigate the effect of pre-sowing and scarification treatments on seed germination and seedling growth of guava (Psidium guajava L.) in the laboratories of the Department of Seed Science and Technology, CCS HAU, Hisar during the year 2015. There were three scarification methods with different treatments under study, i.e. water soaking (for 24, 48 and 72 hr), hot water soaking (at 70, 80, 90 and 100ÂºC) and sulphuric acid soaking (at 10, 20, 30, 40 and 50% concentration). Duration for hot water soaking and sulphuric acid soaking was kept as quick dip (5 seconds), 1 min. and 3 min. The study revealed that pre soaking the seeds in hot water and sulphuric acid greatly increased germination, especially soaking of seeds in 20% sulphuric acid solution for 3 min., which showed up to 72% germination. Parameters like germination%, mean germination time, seedling length and seedling vigour were positively affected by all the scarification treatments. Seed viability decreased but the standard germination efficiently increased due to scarification treatments. Hot water soaking at 80ÂºC temperature for 1 min. improved germination and resulted in maximum seedling length (6.03 cm) in laboratory. Seeds treated with higher sulphuric acid concentrations or soaked in hot water at higher temperature showed poor germination as well as poor vigour. Seeds without any scarification treatment showed poor germination.